On the renewal of a solution of the Dirichlet boundary-value problem for a biharmonic equation - Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study the problem of renewal of a solution of the Dirichlet boundary-value problem for a biharmonic equation on the basis of the known information about the boundary function. The obtained estimates of renewal error are unimprovable in certain cases.